2015
DOI: 10.3389/fmicb.2015.00949
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory principles governing Salmonella and Yersinia virulence

Abstract: Enteric pathogens such as Salmonella and Yersinia evolved numerous strategies to survive and proliferate in different environmental reservoirs and mammalian hosts. Deciphering common and pathogen-specific principles for how these bacteria adjust and coordinate spatiotemporal expression of virulence determinants, stress adaptation, and metabolic functions is fundamental to understand microbial pathogenesis. In order to manage sudden environmental changes, attacks by the host immune systems and microbial competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 221 publications
(318 reference statements)
0
39
0
Order By: Relevance
“…Notably, the main mechanism used by Salmonella to adapt to environmental conditions during the initial passage through the host gut are encoded in the core genome, which acts independent of the genes acquired by HGT, including the virulence genes encoded in SPIs. These regulatory systems encoded within these SPIs comprise, among others, the activation of ATR systems [41][42][43], systems related to survival under limitation of nutrient step [44,45], tolerance to hyperosmolarity and anaerobic environments [46][47][48], as well as quorum sensing [49]. Although initially these systems are responsible for the adaptation to the adverse intestinal environment of the host, some of them (such as the two-component systems PhoPQ and PmrAB, or the OmpR protein) are also responsible for the activation of genes encoded within the pathogenicity islands and other HGT elements, to ensure the passage through the intestinal barrier [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the main mechanism used by Salmonella to adapt to environmental conditions during the initial passage through the host gut are encoded in the core genome, which acts independent of the genes acquired by HGT, including the virulence genes encoded in SPIs. These regulatory systems encoded within these SPIs comprise, among others, the activation of ATR systems [41][42][43], systems related to survival under limitation of nutrient step [44,45], tolerance to hyperosmolarity and anaerobic environments [46][47][48], as well as quorum sensing [49]. Although initially these systems are responsible for the adaptation to the adverse intestinal environment of the host, some of them (such as the two-component systems PhoPQ and PmrAB, or the OmpR protein) are also responsible for the activation of genes encoded within the pathogenicity islands and other HGT elements, to ensure the passage through the intestinal barrier [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…It has been relatively well established that although Y. enterocolitica strains possess the same virulence factors, their expression profiles can differ significantly (Schmühl et al, 2019). This may be the consequence of the finding that even small alterations in the content and organization of the genetic information may alter the expression pattern of virulence genes and their regulators in response to environmental factors (Uliczka et al, 2011;Erhardt and Dersch, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Yersinia enterocolitica synthesizes numerous virulence factors that are active at different stages of an infection and whose expression is altered according to the diverse growth conditions experienced by these bacteria in mammalian hosts (Straley and Perry, 1995;Marceau, 2005;Erhardt and Dersch, 2015;Chen et al, 2016). It was previously demonstrated that a functional urease is essential for the survival of Y. enterocolitica O:9 during passage through the stomach (De Koning-Ward and Robins-Browne, 1995;Young et al, 1996), and is also necessary for full virulence in oral infections in the rat model (Gripenberg-Lerche et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, plasmid-encoded adhesins have so far not often been reported in lactobacilli except for a study on the probiotic intestinal strain L. paracasei NFBC338 which encodes for a collagen-binding protein (CD00222) on one of its plasmids20. In contrast, plasmid-encoded adhesins and virulence factors that are well-characterized are found especially in enteropathogenic strains such as Yersinia and Salmonella 21. The plasmid location of the msl gene could suggest that it is a recently acquired property of L. plantarum CMPG5300 through horizontal gene transfer.…”
Section: Discussionmentioning
confidence: 99%